Unifiedcamp

Author

Unifiedcamp 113

Leave a reply

Post your answer

Answers ( 1 )

  1. User
    6/16/2020

    Step1:p(1)

    Step2: p(k)

    Step3: p(k+1)

    Step1: p(1) assume that n=1 

    RHS= n(n+1)÷2

    1(1+1)÷2 =1(2)÷2 = 2÷2= 1

    P(1) is true

    Step2: p(k) is true by assumption, assume n=k

    1+2+3+..+k=k(k+1)÷2

    Step3: p(k+1)

    Add k+1 to both sides

    1+2+3+....+k+k+1= k(k+1)÷2 + k+1

     (K+1) {k÷2 + 1÷1}

    (K+1) {k+2÷2}

    (K+1) {k+2}÷2

    (K+1) {k+1+1}÷2

    Assume n=(k+1)

    n=(n+1)÷2 

    Peace67

    Good Answer